Decreased SATB2 expression is associated with metastasis and poor prognosis in human clear cell renal cell carcinoma - Guo, Changcheng (Int J Clin Exp Pathol, 2015)
In this study, we investigate the expression and role of special AT-rich sequence-binding protein-2 (SATB2) in clear cell renal cell carcinoma (ccRCC) tissue, and to evaluate the clinical and prognostic significance of SATB2 protein in patients with ccRCC. The expression of SATB2 and SATB1 was examined in ccRCC tissue by Western blotting, real-time PCR and immunohistochemical staining. The association between clinicopathological features and SATB2 level was investigated. The correlation of SATB2 expression with overall survival was also analyzed. The expression of SATB2 protein in tumor tissues was much lower than that in paired normal tissues. The overall survival of the patients with high SATB2 expression was significantly higher than that of the low SATB2 expression group. Low or negative SATB2 expression was significantly correlated with AJCC staging and Furman grade in ccRCC. In contrast, the expression of SATB1 was significantly higher in adjacent tumor tissue than that in normal and tumor tissues. This study provides the first evidence of the expression and clinical significance of SATB2 in ccRCC. Our data suggest that SATB2 functions as a tumor suppressor in the development and progression of ccRCC, and is thereby implicated as a valuable prognostic marker for ccRCC patients.